Keanekaragaman Spesies Nyamuk Genus Tripteroides (Diptera: Culicidae) di Indonesia - Nugroho, Sidiq Setyo; Mujiyono, Mujiyono (Al-Kauniyah: Jurnal Biologi, 2021)
dari 21 genus nyamuk yang terdapat di Indonesia. Tripteroides termasuk dalam Tribe Sabethini bersama dengan genus Kimia, Malaya dan Topomyia, Empat dari lima subgenus dalam genus Tripteroides terdapat di Indonesia, yaitu Polylepidomyia, Rachionotomyia, Rachisoura, dan Tripteroides. Tujuan studi ini adalah memperbarui daftar spesies, sebaran, informasi perkembangan taksonomi dalam genus Tripteroides di Indonesia serta kunci identifikasi spesies untuk nyamuk betinanya. Data dikumpulkan dengan studi literatur dan menghimpun laporan penelitian nasional riset khusus vektor dan reservoir penyakit (Rikhus Vektora). Tercatat sebanyak 47 spesies nyamuk Tripteroides di Indonesia dan sebagian besar (33 spesies) merupakan spesies endemik Papua. Terdapat penambahan sebanyak empat spesies dibanding data spesies yang diterbitkan sebelumnya. Penemuan Tp. affinis dari Rikhus Vektora menjadi catatan spesies baru anggota genus Tripteroides di Indonesia. Spesies Tp. tenax, Tp. nepethisimilis dan Tp. littlechildi pernah tercatat terdapat di Indonesia oleh beberapa literatur, namun belum dimasukkan dalam daftar spesies sebelumnya. Kunci identifikasi untuk nyamuk betina juga disampaikan dalam artikel ini.AbstractThe genus Tripteroides is one of 21 genera of mosquitoes found in Indonesia. Tripteroides belongs to the Tribe Sabethini along with the genera Kimia, Malaya, and Topomyia. Four of the five subgenera of Tripteroides are found in Indonesia, namely Polylepidomyia, Rachionotomyia, Rachisoura, and Tripteroides. The purpose of writing this article is to update the species list, distribution, taxonomic development information in the genus Tripteroides in Indonesia, and the species identification key for female mosquitoes. Data were collected by literature study and from reports of national special research for vector and reservoir of disease (Rikhus Vektora). There are 47 species of Tripteroides mosquitoes present in Indonesia and mostly (33 species) were endemic species in Papua. There was an addition of four species compared to the previously published checklist. Collection of Tp. affinis from Rikhus Vektora has become a new record of the genus Tripteroides member in Indonesia. Tp. tenax, Tp. nepethisimilis and Tp. littlechildi had been recorded in Indonesia by some literature. However, those three species have not been included in the previous checklist yet. An identification key for female mosquitoes is also provided here.Â